Enamel veneering repair material and preparation method thereof
By combining zirconia, alumina and other materials in specific proportions, the problem of insufficient durability and aesthetics of existing dental veneers is solved, and high hardness, wear resistance and good biocompatibility are achieved. , reduces the risk of porcelain collapse and shedding, and improves the user experience.
Patent Information
- Application Number
- CN202411325092.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-09-23
AI Technical Summary
The existing dental veneer materials have insufficient durability, aesthetics and grinding and removal of dental tissue, resulting in high risk of porcelain collapse and shedding, and poor user experience.
Using zirconia, aluminum oxide, hydroxyapatite, dimethyl silylated silica, fluorapatite, thermosetting acrylic resin, aluminum hydroxide gel, silane coupling agent, polyvinyl alcohol, sodium phytate hexaphosphate The materials are combined in a specific proportion and the teeth patches are prepared through special processes to improve adhesion and wear resistance, and reduce the risk of tooth tissue removal and porcelain collapse.
It achieves high hardness, wear resistance and good biocompatibility of the dental patch, reduces the risk of ceramic collapse and shedding, extends the service life, and improves the aesthetic effect and user experience.
Smart Images

Figure BDA0005055193980000121 
Figure BDA0005055193980000131 
Figure BDA0005055193980000151
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic formed products, and in particular relates to a tooth enamel veneer repair material and a preparation method thereof. Background Art
[0002] In daily life, bad oral hygiene habits, diet structure and accidental injuries may lead to various problems with teeth. For example, long-term drinking of colored beverages such as coffee and tea, or bad habits such as smoking, can easily stain the surface of teeth and affect their appearance. In addition, caries, tooth wear, trauma, etc. can also cause damage to the morphology and structure of teeth. Problems such as tooth defects and discoloration are becoming increasingly common. Although traditional restoration methods such as fillings can solve some problems, they are often unsatisfactory in terms of aesthetics and durability.
[0003] Having neat and white teeth is not only good for oral health, but also improves personal image and self-confidence. In social and professional occasions, beautiful teeth have become a need for more and more people. As people pay more and more attention to oral health and aesthetics, the requirements for tooth restoration technology are also getting higher and higher. With the continuous development of tooth restoration technology, enamel veneer restoration materials (i.e., tooth veneers) have been born and play an important role in the field of stomatology. Enamel veneer restoration materials can significantly improve the appearance of teeth without damaging too much tooth tissue, satisfying people's pursuit of beauty. For example, patent CN208031312U discloses a tooth veneer that wraps the tooth surface, protects the teeth, and improves aesthetics.
[0004] The existing types of dental veneers are mainly resin veneers, porcelain veneers, and hard resin veneers. Resin veneers are low in price, but have poor durability, are prone to aging and discoloration, are easy to wear, and are difficult to clean. Porcelain veneers have the advantages of strong wear resistance, not easy to be allergic, and have beautiful and stable colors, but they have the problem of relatively large amount of tooth tissue removal, which can cause tooth sensitivity. When hit by a large external force or biting hard objects, ceramic veneers may break, and the replacement cost is high. Although hard resin veneers have the advantage of better wear resistance than resin veneers, they are still slightly inferior to porcelain veneers in terms of beauty and durability. They still need to remove a large amount of tooth tissue, which can cause problems such as tooth sensitivity.
[0005] Therefore, it is necessary to develop new dental veneer materials that can further improve adhesion, reduce the amount of tooth tissue removed, reduce the risk of porcelain chipping and falling off, and provide a better user experience while ensuring good biocompatibility, high hardness and wear resistance. Summary of the invention
[0006] In order to further improve the adhesion of tooth veneer materials, reduce the amount of tooth tissue removed, and reduce the risk of porcelain collapse and falling off, and provide a better user experience. The present invention provides a tooth enamel veneer repair material and a preparation method thereof, using zirconium oxide, aluminum oxide, hydroxyapatite, silica dimethyl silylate, silicon dioxide, fluoroapatite, magnesium oxide, thermosetting acrylic resin, aluminum hydroxide gel, silane coupling agent, polyvinyl alcohol, sodium inositol hexaphosphate, etc. as raw materials, various components are matched in a certain proportion, and a special process is used to prepare tooth veneers. While ensuring good biocompatibility, high hardness, and wear resistance, it can further improve adhesion, reduce the amount of tooth tissue removed, and reduce the risk of porcelain collapse and falling off, extend the service life, and provide a better user experience. Its specific technical scheme is as follows:
[0007] A tooth enamel veneer restoration material comprises the following raw materials in parts by mass: 60 to 70 parts of zirconium oxide, 15 to 20 parts of aluminum oxide, 8 to 12 parts of hydroxyapatite, 5 to 8 parts of silica dimethyl silylate, 3 to 6 parts of silicon dioxide, 0.1 to 0.5 parts of fluoroapatite, 0.3 to 0.5 parts of magnesium oxide, 3 to 6 parts of thermosetting acrylic resin, 3 to 5 parts of aluminum hydroxide gel, 1.5 to 3 parts of silane coupling agent, 0.5 to 1.5 parts of polyvinyl alcohol, and 0.5 to 1.5 parts of sodium inositol hexaphosphate.
[0008] In the above technical solution, the particle sizes of the zirconium oxide, aluminum oxide, hydroxyapatite, silicon dioxide, fluoroapatite and magnesium oxide are all nanometer-sized.
[0009] In the above technical solution, the particle size range of the dimethyl silylate silica is 0.3 μm to 2 μm.
[0010] In the above technical solution, the thermosetting acrylic resin is in liquid state and its model is HK87010.
[0011] In the above technical solution, the model of the silane coupling agent is KH-560, and the particle sizes of the polyvinyl alcohol and sodium phytate are both nanometer-level.
[0012] The method for preparing the above-mentioned enamel veneer repair material comprises the following steps:
[0013] S1: premix zirconium oxide, aluminum oxide, hydroxyapatite, silicon dioxide, fluoroapatite and magnesium oxide according to their mass fractions to obtain a mixture A; premix polyvinyl alcohol and sodium phytate to obtain a mixture B; disperse silica dimethyl silylate uniformly in a thermosetting acrylic resin, and evacuate the mixture to obtain a modified product C;
[0014] S2: Mix the mixture A and the mixture B uniformly, then add the aluminum hydroxide gel and the silane coupling agent, mix uniformly, then add the modified substance C, mix uniformly, and obtain a base material;
[0015] S3: The base material is molded, and cold pressing, isostatic pressing, medium temperature heat treatment, and high temperature heat treatment are performed in sequence to obtain a formed tooth veneer, i.e., a tooth enamel veneer repair material.
[0016] In S3 of the above preparation method, the cold pressing pressure is 8 MPa to 15 MPa, the cold pressing time is 8 s to 15 s, and the cold pressing temperature is 80° C. to 90° C.
[0017] In S3 of the above preparation method, the isostatic pressing pressure is 260 MPa to 280 MPa, the isostatic pressing time is 50 s to 80 s, and the isostatic pressing temperature is 120° C. to 150° C.
[0018] In S3 of the above preparation method, the temperature of the medium-temperature heat treatment is 600° C. to 800° C., and the time of the medium-temperature heat treatment is 30 min to 60 min.
[0019] In S3 of the above preparation method, the temperature of the high temperature heat treatment is 1200° C. to 1400° C., and the time of the high temperature heat treatment is 60 min to 90 min.
[0020] The tooth enamel veneer repair material and preparation method thereof provided by the present invention have the following beneficial effects compared with the prior art:
[0021] 1. The tooth enamel veneer restoration material of the present invention adopts zirconium oxide, aluminum oxide, hydroxyapatite, silica dimethyl silylate, silicon dioxide, fluoroapatite, magnesium oxide, thermosetting acrylic resin, aluminum hydroxide gel, silane coupling agent, polyvinyl alcohol, sodium phytate, etc. as raw materials. Various components are combined in a certain proportion to prepare a tooth veneer. While ensuring good biocompatibility, high hardness and wear resistance, it can further improve adhesion, reduce the amount of tooth tissue removed, and reduce the risk of porcelain collapse and shedding, extend the service life, and provide a better use experience.
[0022] 2. Adding alumina to zirconia ceramics can enhance the overall strength and hardness of the composite material to a certain extent, making the dental veneer more resistant to wear and external impact in daily use and extending its service life. The addition of alumina can improve the microstructure of zirconia ceramics, inhibit crack propagation, thereby improving the toughness of the material and reducing the risk of rupture of the dental veneer when subjected to bite force and other effects. Alumina can act as a flux to reduce the sintering temperature of zirconia ceramics to a certain extent and accelerate the sintering time of ceramic materials, which helps to reduce energy consumption and production costs. It can also reduce the requirements of high temperature on equipment and reduce the structural effects of high temperature on other composite components. The addition of an appropriate amount of alumina can improve the fluidity and formability of zirconia ceramic slurry, making it easier for dental veneers to obtain uniform shapes and sizes during the production process, and improving the quality and precision of the product. By adjusting the content of alumina and the ratio of other additives, the color and transparency of the dental veneer can be fine-tuned to better match the appearance of natural teeth and achieve a more natural and beautiful repair effect. The presence of aluminum oxide can make the surface of the dental veneer smoother and more delicate, reduce the appearance of surface defects such as pores and cracks, and improve the appearance quality and aesthetic performance of the veneer.
[0023] 3. Hydroxyapatite has good compatibility with human tissues and will not cause allergic reactions or rejection reactions. Adding it to zirconia ceramic tooth veneers can improve overall biocompatibility, reduce stimulation to oral tissues, and reduce the risk of adverse reactions. Hydroxyapatite is the main inorganic component of teeth. For the part of the tooth surface that has been demineralized due to caries and other reasons, adding hydroxyapatite can provide calcium and phosphorus ions in the oral environment, which is helpful for the remineralization process of the tooth surface, so that the damaged enamel can be repaired and strengthened to a certain extent, and the tooth's anti-caries ability can be improved. Hydroxyapatite can improve the microstructure of zirconia ceramics, inhibit crack propagation, thereby improving the toughness of the material and reducing the risk of tooth veneers breaking when subjected to bite forces and other effects. The color of hydroxyapatite is similar to the natural color of teeth. Adding it to zirconia ceramics can make the color of the tooth veneer more natural and realistic, better blend with the surrounding natural teeth, and improve the aesthetic effect after repair.
[0024] 4. Silica dimethyl silylate can increase the silicon content on the surface of zirconia ceramics, making it easier to react chemically with adhesives to form strong chemical bonds, thereby increasing the bonding strength between the dental veneer and the tooth surface, reducing the risk of veneer shedding, and effectively reducing the amount of tooth tissue removed. Silica dimethyl silylate with an appropriate content and particle size can help improve the wettability of the zirconia ceramic surface, allowing the adhesive to spread and penetrate better on its surface, further enhancing the bonding effect. The appropriate addition of silica dimethyl silylate can greatly reduce the thermal expansion coefficient of ceramic dental veneers, and when used in combination with other ingredients, it can improve the aging resistance of ceramic dental veneers; it can also help with the color stability of dental veneers, reducing the color fading or discoloration caused by various factors in the oral environment (such as food, beverages, oral secretions, etc.).
[0025] 5. Silicon dioxide can play a role of dispersion strengthening in the zirconium oxide ceramic matrix, inhibit crack propagation, improve the strength and toughness of the tooth patch, make it more able to withstand chewing pressure, and reduce the risk of breakage or damage. Adding a proper amount of silicon dioxide can increase the hardness of the material, making it more wear-resistant, and can also adjust the elastic modulus, so that the mechanical properties of the tooth patch and natural teeth are more matched, providing a more comfortable use experience.
[0026] The silanol (-Si-OH) formed on the surface of the veneer reacts chemically with the active ingredients in the adhesive to form a chemical bond, thereby increasing the bonding strength between the veneer and the tooth surface and reducing the possibility of the veneer falling off. Silica can also adjust the transparency and color of the veneer, allowing the veneer to better simulate the appearance of natural teeth.
[0027] 6. Fluorapatite has a similar structure to hydroxyapatite, a natural component of human teeth, and has good biocompatibility. Adding it to zirconia ceramic tooth veneers can make it get along more harmoniously with human oral tissues and reduce stimulation and adverse reactions to oral mucosa and other tissues. In the oral environment, fluoride ions can be released from fluorapatite and combine with minerals such as calcium and phosphorus on the surface of the teeth to promote the remineralization of the hard tissues of the teeth, enhance the anti-caries ability of the teeth, and help prevent caries lesions of the tooth tissues around the veneers. Fluorapatite can play a role of diffusion strengthening in the zirconia ceramic matrix, inhibit crack propagation, improve the strength and toughness of the tooth veneer, make it more able to withstand chewing pressure, and reduce the risk of breakage or damage. The optical properties of fluorapatite, such as the refractive index, cooperate with zirconia ceramics to allow light to pass or scatter better, making the color and transparency of the tooth veneer closer to natural teeth.
[0028] 7. Magnesium oxide can be used as a stabilizer. When added to zirconium oxide crystals, it can transform the crystal form of zirconium oxide from monoclinic phase (m) to tetragonal phase (t), so that zirconium oxide can maintain crystal stability at different temperatures, especially during high heat cycles, thereby improving the stability and anti-aging properties of the tooth patch. At the same time, it can also inhibit grain growth, increase the density of the tooth patch, make it denser, and thus improve strength and toughness, and better withstand chewing pressure. Magnesium oxide has good biocompatibility with human tissues. Adding it to zirconium oxide ceramic tooth patches can make it get along more harmoniously with human oral tissues and reduce irritation and adverse reactions to oral mucosa and other tissues.
[0029] 8. Adding thermosetting acrylic resin to zirconia ceramic tooth veneers has the following main effects: Thermosetting acrylic resin has good bonding properties, can increase the compaction density of the base material, make the various component materials tightly combined, and can fill the pores on the surface of the particles and between the particles, eliminate bubbles, and improve the performance of the tooth veneer. After short-term sintering, the thermosetting acrylic resin has good bonding with other ingredients, which can increase the toughness of the zirconia ceramic tooth veneer, making it more able to withstand various mechanical effects in the mouth, reduce the risk of rupture or damage to the veneer, and enhance the resistance to microcracks and durability. After the thermosetting acrylic resin is heat-treated, the volatile substances are discharged, which is safe and non-irritating, and does not affect the color aesthetics.
[0030] 9. Aluminum hydroxide gel can increase the compaction density of the material, fill the pores on the surface of particles and between particles, eliminate bubbles, improve the compaction quality of the base material, participate in the reaction during the heat treatment sintering process, help to improve the sintering density of ceramic tooth veneers, improve the flexural strength, Vickers hardness, fracture toughness, and reduce the thermal expansion coefficient.
[0031] Aluminum hydroxide gel helps to disperse and relieve stress concentration inside zirconia ceramics, reduce the generation and expansion of cracks caused by stress concentration, and improve the overall strength and durability of dental veneers. The components retained by aluminum hydroxide gel after heat treatment can coexist more harmoniously with human oral tissues, reduce irritation and adverse reactions to oral mucosa and other tissues, and reduce the risk of allergies.
[0032] 10. Some functional groups (such as alkoxy) in the silane coupling agent molecule can undergo hydrolysis reaction with the hydroxyl groups on the surface of zirconia ceramics to form chemical bonds, making them tightly bonded; the organic functional group at the other end can react with the binder resin, thereby building a "bridge" between zirconia ceramics and the binder, firmly connecting the two materials of different properties together, greatly improving the bonding strength, and preventing the dental veneer from falling off in the mouth. Silane coupling agents can reduce the surface tension between zirconia ceramics and the binder, allowing the binder to better wet the surface of zirconia ceramics, increase the contact area, and further improve the bonding effect. It can prevent moisture from penetrating into the bonding interface to a certain extent, reduce the aging and degradation of the binder caused by moisture, and thus improve the durability of the dental veneer repair and extend its service life. The oral environment is complex, with saliva, food residues, bacteria, etc. Silane coupling agents can enhance the stability of the binder and zirconia ceramics in the oral environment, so that it can better withstand the influence of factors such as chewing force and temperature changes, and maintain long-term bonding performance.
[0033] 11. In the process of making tooth veneers, polyvinyl alcohol is used as an auxiliary material to help zirconia ceramics to be better formed, improve production efficiency and product quality. Polyvinyl alcohol can improve the surface compatibility of granular materials. When mixing and pressurizing, polyvinyl alcohol can make granular materials easier to combine with thermosetting acrylic resins and silane coupling agents, thereby improving the molding quality. Polyvinyl alcohol interacts with the components in thermosetting acrylic resins and silane coupling agents to adjust properties such as viscosity and fluidity, making it easier for the base material to expel gas and excess liquid under pressure, ensuring that the liquid is fully and evenly filled, and improving the quality uniformity of cold pressing and isostatic pressing. Adjust the drying speed of the material to avoid problems such as cracking caused by too fast drying, so that the tooth veneer is more stable during the heat treatment drying process.
[0034] 12. Sodium phytate can reduce the adhesion of oral bacteria on the surface of dental veneers, reducing the risk of oral diseases such as caries and periodontitis. By interacting with ions or proteins on the surface of bacteria, it changes the surface properties of bacteria, making it difficult for them to adhere to the patch, and has a certain inhibitory effect on the formation of dental calculus. As an antioxidant, sodium phytate can protect zirconium oxide ceramics and tooth tissues from damage by oxidative stress, maintaining the stability and color durability of dental veneers. After the sintering reaction, sodium phytate can greatly improve the anti-aging properties of ceramic dental veneers.
[0035] 13. In the preparation method of the present invention, firstly, silica dimethyl silylate is uniformly dispersed in a thermosetting acrylic resin, and the gas is evacuated to obtain a modified product C; the thermosetting acrylic resin is used to pre-modify the surface of silica dimethyl silylate, and the gas is exhausted, and a layer of thermosetting acrylic resin is adhered to the surface, which can improve the surface adhesion of silica dimethyl silylate and the bonding between the two, and better play the superposition effect of silica dimethyl silylate and thermosetting acrylic resin. After final mixing, the quality and stress of the tooth veneer are more uniform, and the performance of the tooth veneer is further improved.
[0036] 14. The temperature design of cold pressing and isostatic pressing of the present invention can improve the compaction and bonding of the base material, the uniformity and smoothness of liquid discharge, and the compaction homogeneity, thereby improving the quality of medium-temperature heat treatment and high-temperature heat treatment, thereby improving the performance of the tooth veneer. DETAILED DESCRIPTION
[0037] The present invention is further described below in conjunction with specific implementation cases, but the present invention is not limited to these embodiments.
[0038] Example 1
[0039] A tooth enamel veneer restoration material comprises the following raw materials in parts by mass: 65 parts of zirconium oxide, 18 parts of aluminum oxide, 10 parts of hydroxyapatite, 6.5 parts of silica dimethyl silylate, 5 parts of silicon dioxide, 0.3 parts of fluoroapatite, 0.4 parts of magnesium oxide, 4.5 parts of thermosetting acrylic resin, 4 parts of aluminum hydroxide gel, 2.5 parts of silane coupling agent, 1 part of polyvinyl alcohol, and 1 part of sodium inositol hexaphosphate.
[0040] The method for preparing the above-mentioned enamel veneer repair material comprises the following steps:
[0041] S1: premix zirconium oxide, aluminum oxide, hydroxyapatite, silicon dioxide, fluoroapatite and magnesium oxide according to their mass fractions to obtain a mixture A; premix polyvinyl alcohol and sodium phytate to obtain a mixture B; disperse silica dimethyl silylate uniformly in a thermosetting acrylic resin, and evacuate the mixture to obtain a modified product C;
[0042] S2: Mix the mixture A and the mixture B uniformly, then add the aluminum hydroxide gel and the silane coupling agent, mix uniformly, then add the modified substance C, mix uniformly, and obtain a base material;
[0043] S3: The base material is molded and cold pressed at a pressure of 12 MPa, a time of 10 s, and a temperature of 85°C. It is then isostatically pressed at a pressure of 270 MPa, a time of 60 s, and a temperature of 130°C. It is then heat treated at 700°C for 45 min, and then heat treated at 1300°C for 75 min. The base material is cooled, trimmed, polished, and cleaned to obtain a formed tooth veneer, i.e., a tooth enamel veneer repair material.
[0044] Example 2
[0045] A tooth enamel veneer restoration material comprises the following raw materials in parts by mass: 60 parts of zirconium oxide, 15 parts of aluminum oxide, 8 parts of hydroxyapatite, 5 parts of silica dimethyl silylate, 3 parts of silicon dioxide, 0.1 parts of fluoroapatite, 0.3 parts of magnesium oxide, 3 parts of thermosetting acrylic resin, 3 parts of aluminum hydroxide gel, 1.5 parts of silane coupling agent, 0.5 parts of polyvinyl alcohol, and 0.5 parts of sodium inositol hexaphosphate.
[0046] The method for preparing the above-mentioned enamel veneer repair material comprises the following steps:
[0047] S1: premix zirconium oxide, aluminum oxide, hydroxyapatite, silicon dioxide, fluoroapatite and magnesium oxide according to their mass fractions to obtain a mixture A; premix polyvinyl alcohol and sodium phytate to obtain a mixture B; disperse silica dimethyl silylate uniformly in a thermosetting acrylic resin, and evacuate the mixture to obtain a modified product C;
[0048] S2: Mix the mixture A and the mixture B uniformly, then add the aluminum hydroxide gel and the silane coupling agent, mix uniformly, then add the modified substance C, mix uniformly, and obtain a base material;
[0049] S3: The base material is molded and cold pressed at a pressure of 8 MPa, a time of 8 s, and a temperature of 82°C. It is then isostatically pressed at a pressure of 260 MPa, a time of 50 s, and a temperature of 120°C. It is then heat treated at 600°C for 30 min, and then heat treated at 1200°C for 60 min. The base material is cooled, trimmed, polished, and cleaned to obtain a formed tooth veneer, i.e., a tooth enamel veneer repair material.
[0050] Example 3
[0051] A tooth enamel veneer restoration material comprises the following raw materials in parts by mass: 62 parts of zirconium oxide, 16 parts of aluminum oxide, 9 parts of hydroxyapatite, 6 parts of silica dimethyl silylate, 4 parts of silicon dioxide, 0.2 parts of fluoroapatite, 0.35 parts of magnesium oxide, 3.5 parts of thermosetting acrylic resin, 3.5 parts of aluminum hydroxide gel, 1.8 parts of silane coupling agent, 0.8 parts of polyvinyl alcohol, and 0.6 parts of sodium inositol hexaphosphate.
[0052] The method for preparing the above-mentioned enamel veneer repair material comprises the following steps:
[0053] S1: premix zirconium oxide, aluminum oxide, hydroxyapatite, silicon dioxide, fluoroapatite and magnesium oxide according to their mass fractions to obtain a mixture A; premix polyvinyl alcohol and sodium phytate to obtain a mixture B; disperse silica dimethyl silylate uniformly in a thermosetting acrylic resin, and evacuate the mixture to obtain a modified product C;
[0054] S2: Mix the mixture A and the mixture B uniformly, then add the aluminum hydroxide gel and the silane coupling agent, mix uniformly, then add the modified substance C, mix uniformly, and obtain a base material;
[0055] S3: The base material is molded and cold pressed at a pressure of 9 MPa, a time of 9 s, and a temperature of 84°C. It is then isostatically pressed at a pressure of 265 MPa, a time of 60 s, and a temperature of 125°C. It is then heat treated at 650°C for 40 min, and then heat treated at 1250°C for 70 min. The base material is cooled, trimmed, polished, and cleaned to obtain a formed tooth veneer, i.e., a tooth enamel veneer repair material.
[0056] Example 4
[0057] A tooth enamel veneer restoration material comprises the following raw materials in parts by mass: 68 parts of zirconium oxide, 19 parts of aluminum oxide, 11 parts of hydroxyapatite, 7 parts of silica dimethyl silylate, 5 parts of silicon dioxide, 0.4 parts of fluoroapatite, 0.45 parts of magnesium oxide, 5.5 parts of thermosetting acrylic resin, 4.5 parts of aluminum hydroxide gel, 2.5 parts of silane coupling agent, 1.2 parts of polyvinyl alcohol, and 1.4 parts of sodium inositol hexaphosphate.
[0058] The method for preparing the above-mentioned enamel veneer repair material comprises the following steps:
[0059] S1: premix zirconium oxide, aluminum oxide, hydroxyapatite, silicon dioxide, fluoroapatite and magnesium oxide according to their mass fractions to obtain a mixture A; premix polyvinyl alcohol and sodium phytate to obtain a mixture B; disperse silica dimethyl silylate uniformly in a thermosetting acrylic resin, and evacuate the mixture to obtain a modified product C;
[0060] S2: Mix the mixture A and the mixture B uniformly, then add the aluminum hydroxide gel and the silane coupling agent, mix uniformly, then add the modified substance C, mix uniformly, and obtain a base material;
[0061] S3: The base material is molded and cold pressed at a pressure of 14 MPa, a time of 12 s, and a temperature of 88°C. It is then isostatically pressed at a pressure of 275 MPa, a time of 70 s, and a temperature of 140°C. It is then heat treated at 750°C for 50 min and then at 1350°C for 80 min. It is then cooled, trimmed, polished, and cleaned to obtain a formed tooth veneer, i.e., a tooth enamel veneer repair material.
[0062] Example 5
[0063] A tooth enamel veneer restoration material comprises the following raw materials in parts by mass: 70 parts of zirconium oxide, 20 parts of aluminum oxide, 12 parts of hydroxyapatite, 8 parts of silica dimethyl silylate, 6 parts of silicon dioxide, 0.5 parts of fluoroapatite, 0.5 parts of magnesium oxide, 6 parts of thermosetting acrylic resin, 5 parts of aluminum hydroxide gel, 3 parts of silane coupling agent, 1.5 parts of polyvinyl alcohol, and 1.5 parts of sodium inositol hexaphosphate.
[0064] The method for preparing the above-mentioned enamel veneer repair material comprises the following steps:
[0065] S1: premix zirconium oxide, aluminum oxide, hydroxyapatite, silicon dioxide, fluoroapatite and magnesium oxide according to their mass fractions to obtain a mixture A; premix polyvinyl alcohol and sodium phytate to obtain a mixture B; disperse silica dimethyl silylate uniformly in a thermosetting acrylic resin, and evacuate the mixture to obtain a modified product C;
[0066] S2: Mix the mixture A and the mixture B uniformly, then add the aluminum hydroxide gel and the silane coupling agent, mix uniformly, then add the modified substance C, mix uniformly, and obtain a base material;
[0067] S3: The base material is molded and cold pressed at a pressure of 15 MPa, a time of 15 s, and a temperature of 90°C. It is then isostatically pressed at a pressure of 280 MPa, a time of 80 s, and a temperature of 150°C. It is then heat treated at 800°C for 60 min and then at 1400°C for 90 min. The base material is cooled, trimmed, polished, and cleaned to obtain a formed tooth veneer, i.e., a tooth enamel veneer repair material.
[0068] The particle sizes of zirconium oxide, aluminum oxide, hydroxyapatite, silicon dioxide, fluoroapatite and magnesium oxide used in the above embodiments are all nanometers. The particle size range of dimethyl silylated silica is 0.3μm to 2μm. Thermosetting acrylic resin is liquid, model HK87010, Shanghai Kaiyin Chemical Co., Ltd. Aluminum hydroxide gel is a white viscous substance, Inner Mongolia Xinhong Biotechnology Co., Ltd. The model of silane coupling agent is KH-560, Dongguan Dinghai Plastic Chemical Co., Ltd. The particle size of polyvinyl alcohol is all nanometers, model BP-26, Changchun Chemical (Jiangsu) Co., Ltd. The particle size of sodium inositol hexaphosphate is nanometers, Shandong Liyuan Biotechnology Co., Ltd.
[0069] Comparative Example 1
[0070] In the raw materials, the addition amount of hydroxyapatite is 5 parts, and the addition amount of zirconium oxide is 70 parts; other methods and parameters are the same as in Example 1.
[0071] Comparative Example 2
[0072] No silica dimethyl silylate was added to the raw materials, and the content of silica dimethyl silylate was replaced by zirconium oxide; other methods and parameters were the same as in Example 1.
[0073] Comparative Example 3
[0074] In the raw materials, the addition amount of silica dimethyl silylate is 2.5 parts, and the addition amount of zirconium oxide is 69 parts; other methods and parameters are the same as in Example 1.
[0075] Comparative Example 4
[0076] Among the raw materials, the amount of thermosetting acrylic resin added was 1.5 parts, and the amount of zirconium oxide added was 68 parts; other methods and parameters were the same as in Example 1.
[0077] Comparative Example 5
[0078] Among the raw materials, the addition amount of silica dimethyl silylate is 2.5 parts, the addition amount of thermosetting acrylic resin is 1.5 parts, and the addition amount of zirconium oxide is 72 parts; other methods and parameters are the same as in Example 1.
[0079] Comparative Example 6
[0080] In the raw material, the particle size range of dimethyl silylate silica is 0.05 μm to 0.5 μm; other methods and parameters are the same as in Example 1.
[0081] Comparative Example 7
[0082] In the raw materials, no aluminum hydroxide gel is added, and the content of the aluminum hydroxide gel is replaced by zirconium oxide; other methods and parameters are the same as in Example 1.
[0083] Comparative Example 8
[0084] In the raw materials, sodium phytate was not added, and the content of sodium phytate was replaced by zirconium oxide; other methods and parameters were the same as those in Example 1.
[0085] Comparative Example 9
[0086] In the preparation method, silica dimethyl silylate participates in the mixed preparation of mixture A, that is, silica dimethyl silylate is not mixed and modified with thermosetting acrylic resin, and in S2, the modified substance C directly adopts thermosetting acrylic resin; other methods and parameters are the same as Example 1.
[0087] Comparative Example 10
[0088] In the preparation method, the temperature of cold pressing is 25° C. (normal temperature), and the temperature of isostatic pressing is 25° C. (normal temperature); other methods and parameters are the same as in Example 1.
[0089] The performance of the tooth veneers (tooth enamel veneer repair materials) prepared in the above-mentioned embodiments and comparative examples was tested.
[0090] 1. Performance Testing
[0091] The flexural strength test was carried out according to the GB30367 method; the Vickers hardness was tested by a Vickers hardness tester according to the GB / T4340 method; the fracture toughness was tested by a single-sided V-groove beam method; the thermal expansion coefficient was tested by a thermal expansion instrument at a simulated human body temperature of 37°C; the aging performance test conditions were 135°C aging for 5h, and the monoclinic phase content was tested by XRD. The test results are shown in Table 1 below.
[0092] Table 1 Performance test results
[0093]
[0094]
[0095] It can be seen from the above results that the ceramic tooth veneers of Examples 1 to 5 have good performance, maintain high flexural strength, Vickers hardness, fracture toughness, reduced thermal expansion coefficient, and anti-aging. From the results of Comparative Example 1, it can be seen that the appropriate addition of hydroxyapatite in combination with other ingredients can improve the toughness of the ceramic tooth veneer, and reducing the hydroxyapatite content will significantly reduce the fracture toughness. From the results of Comparative Examples 2 and 3, it can be seen that the appropriate addition of dimethyl silylated silica can well reduce the thermal expansion coefficient of the ceramic tooth veneer, and the use of other ingredients can improve the aging resistance of the ceramic tooth veneer. From the results of Comparative Example 4, it can be seen that adding an appropriate amount of thermosetting acrylic resin can enhance the bonding tightness of the components, increase the density, and then improve the flexural strength, Vickers hardness, fracture toughness, reduce the thermal expansion coefficient, and be more resistant to aging. From the results of comparative example 5, it can be seen that the use of an appropriate amount of silica dimethyl silylate and thermosetting acrylic resin can greatly reduce the thermal expansion coefficient and aging resistance of the ceramic tooth patch, and the silica dimethyl silylate and the thermosetting acrylic resin can adjust and balance the bending strength, Vickers hardness and fracture toughness of the ceramic tooth patch; reducing the amount of silica dimethyl silylate and thermosetting acrylic resin does not achieve a good anti-aging and anti-expansion effect. From the results of comparative example 6, it can be seen that reducing the particle size of silica dimethyl silylate has little effect on the physical properties. From the results of comparative example 7, it can be seen that aluminum hydroxide gel can increase the compaction density of the material, participate in the reaction during the sintering process, and then help to increase the sintering density of the ceramic tooth patch, improve the bending strength, Vickers hardness, fracture toughness, and reduce the thermal expansion coefficient. From the results of comparative example 8, it can be seen that sodium inositol hexaphosphate can well improve the aging resistance of the ceramic tooth patch after the sintering reaction. From the results of Comparative Example 9, it can be seen that if dimethyl silylated silica is not mixed and modified with thermosetting acrylic resin, the performance of dimethyl silylated silica will be affected, thereby affecting the decrease in flexural strength, Vickers hardness, and fracture toughness, as well as the increase in thermal expansion coefficient and poor aging resistance. From the results of Comparative Example 10, it can be seen that the decrease in the temperature of cold pressing and isostatic pressing will affect the compaction and bonding of the base material, as well as the quality of medium-temperature heat treatment and high-temperature heat treatment, thereby affecting the performance degradation.
[0096] 2. In vitro adhesion test
[0097] The preparation thickness of the tooth patch sample is 0.10mm; the tooth model uses discarded human teeth removed from the hospital. The mounting method uses the existing conventional mounting method, grinding and etching the discarded teeth to remove part of the enamel, removing a thickness of 0.14mm, and using light-curing resin to bond the tooth patch to the treated discarded teeth. After 24 hours of bonding, the test is carried out: hammer the teeth to a crushed state, take the tooth patch to blow away the dust, rinse with water, dry, and observe the bonding state of the veneer of the tooth patch and the tooth components. A certain commercially available ceramic patch (alumina ceramic tooth patch) was used for comparative experiments. Three parallel samples were made for each type, and the average value was taken. The test results are shown in Table 2 below.
[0098] Table 2 Adhesion test results
[0099] Sample Adhesion evaluation level Sample Adhesion evaluation level Example 1 1 Comparative Example 1 2 Example 2 1 Comparative Example 2 4 Example 3 1 Comparative Example 3 3 Example 4 1 Comparative Example 4 2 Example 5 1 Comparative Example 5 4 Commercially available ceramic patches 4 Comparative Example 6 2 Comparative Example 7 1 Comparative Example 8 1 Comparative Example 9 2 Comparative Example 10 1
[0100] Evaluation level: 1-The area of the tooth component bonded by the veneer of the dental veneer is greater than 90% and less than or equal to 100%; 2-The area of the tooth component bonded by the veneer of the dental veneer is greater than 80% and less than or equal to 90%; 3-The area of the tooth component bonded by the veneer of the dental veneer is greater than 70% and less than or equal to 80%; 4-The area of the tooth component bonded by the veneer of the dental veneer is greater than 60% and less than or equal to 70%; 5-The area of the tooth component bonded by the veneer of the dental veneer is greater than 50% and less than or equal to 60%; 6-The area of the tooth component bonded by the veneer of the dental veneer is greater than 40% and less than or equal to 50%.
[0101] It can be seen from the above results that the tooth veneers prepared in Examples 1 to 5 have excellent biocompatibility and good adhesion, effectively reducing the risk of porcelain collapse and falling off, and can also reduce the grinding and removal thickness of the teeth. Good adhesion can also be achieved at a removal thickness of 0.14 mm. It can be seen from the results of the comparative examples that hydroxyapatite, dimethyl silylated silica, and thermosetting acrylic resin all have a good effect on improving the adhesion of ceramic tooth veneers. The particle size of dimethyl silylated silica also affects the adhesion. The particle size range of methyl silylated silica is 0.3μm to 2μm, which has an improving effect on adhesion. Dimethyl silylated silica is mixed and modified with a thermosetting acrylic resin, and the dimethyl silylated silicon that is exhausted after surface modification has a better effect of promoting adhesion.
[0102] 3. Human Trial Evaluation
[0103] 43 subjects with tooth damage in the anterior teeth area were selected, and a total of 150 teeth in the anterior teeth area of the 43 people needed veneers; the 90 teeth were divided into 15 groups, each with 10 teeth, and each group was pasted with the tooth veneer prepared in each embodiment and comparative example, and the thickness and shape of the tooth veneer were based on the specific tooth shape; after the veneer was applied, the subjects lived a normal life, and the usage of the subjects was collected. The evaluation results are shown in Table 3 below.
[0104] Table 3 Trial evaluation results
[0105]
[0106] It can be seen from the above results that the ceramic tooth veneers prepared in Examples 1 to 5 have good biocompatibility, good adhesion, and are not prone to ceramic chipping and falling off, which effectively improves the user experience of the ceramic tooth veneer and extends its service life.
Claims
1. A tooth enamel veneer repair material, characterized in that: The enamel veneer restoration material includes the following raw materials in parts by mass: 60 to 70 parts of zirconium oxide, 15 to 20 parts of aluminum oxide, 8 to 12 parts of hydroxyapatite, 5 to 8 parts of silica dimethyl silylate, 3 to 6 parts of silicon dioxide, 0.1 to 0.5 parts of fluoroapatite, 0.3 to 0.5 parts of magnesium oxide, 3 to 6 parts of thermosetting acrylic resin, 3 to 5 parts of aluminum hydroxide gel, 1.5 to 3 parts of silane coupling agent, 0.5 to 1.5 parts of polyvinyl alcohol, and 0.5 to 1.5 parts of sodium inositol hexaphosphate.
2. The tooth enamel veneer repair material according to claim 1, characterized in that: The particle sizes of the zirconium oxide, aluminum oxide, hydroxyapatite, silicon dioxide, fluoroapatite and magnesium oxide are all nanometer-level.
3. The tooth enamel veneer repair material according to claim 1, characterized in that: The particle size of the silica dimethyl silylate is in the range of 0.3 μm to 2 μm.
4. The tooth enamel veneer repair material according to claim 1, characterized in that: The thermosetting acrylic resin is in liquid state and its model is HK87010; the model of the silane coupling agent is KH-560; the particle sizes of the polyvinyl alcohol and sodium phytate are both nanometer level.
5. A method for preparing a tooth enamel veneer repair material, used for preparing the tooth enamel veneer repair material according to claim 1, characterized in that: The preparation method comprises the following steps: S1: premix zirconium oxide, aluminum oxide, hydroxyapatite, silicon dioxide, fluoroapatite and magnesium oxide according to their mass fractions to obtain a mixture A; premix polyvinyl alcohol and sodium phytate to obtain a mixture B; disperse silica dimethyl silylate uniformly in a thermosetting acrylic resin, and evacuate the mixture to obtain a modified product C; S2: Mix the mixture A and the mixture B uniformly, then add the aluminum hydroxide gel and the silane coupling agent, mix uniformly, then add the modified substance C, mix uniformly, and obtain a base material; S3: The base material is molded, and cold pressing, isostatic pressing, medium temperature heat treatment, and high temperature heat treatment are performed in sequence to obtain a formed tooth veneer, i.e., a tooth enamel veneer repair material.
6. The method for preparing a tooth enamel veneer repair material according to claim 5, characterized in that: In S3, the cold pressing pressure is 8MPa-15MPa, the cold pressing time is 8s-15s, and the cold pressing temperature is 80°C-90°C.
7. The method for preparing a tooth enamel veneer repair material according to claim 5, characterized in that: In S3, the isostatic pressing pressure is 260 MPa to 280 MPa, the isostatic pressing time is 50 s to 80 s, and the isostatic pressing temperature is 120° C. to 150° C.
8. The method for preparing a tooth enamel veneer repair material according to claim 5, characterized in that: In S3, the temperature of the medium-temperature heat treatment is 600° C. to 800° C., and the time of the medium-temperature heat treatment is 30 min to 60 min.
9. The method for preparing a tooth enamel veneer repair material according to claim 5, characterized in that: In S3, the temperature of the high temperature heat treatment is 1200° C. to 1400° C., and the time of the high temperature heat treatment is 60 min to 90 min.
Citation Information
Patent Citations
Manufacturing method of minimally invasive molar glass porcelain laminate veneer
CN105125413A
Preparation method of enhanced biologic glass bone repair material
CN110152057A
Zirconia ceramic for tooth veneering and preparation method thereof
CN113511894A
Preparation method of thermosetting resin
CN113604117A
Zirconium oxide full-porcelain dental repair material and its preparing method
CN1813654A
Cited By
Heat insulation coating and preparation method thereof
CN119709000A
Thermal insulation coating and preparation method thereof
CN119709000B
